Análisis de la contribución de la productividad minera al bienestar social en el Perú (2015-2022) - Agurto Silva, Elvis (2024)
This study analysed mining productivity and its contribution to social welfare in Peru over the period 2015 to 2022. An explanatory approach and a non-experimental design were employed, using data from the Banco Central de Reserva del Perú, the Boletín Estadístico Minero and INEI. The data covered exports, mining investments and social welfare indicators. After a thorough analysis, it was concluded that there is a weak relationship between the growth of the mining sector and social welfare in the period studied. Despite the economic benefits generated by mining, they did not translate into significant improvements in social indicators. The study underlines the importance of strategies that balance economic development with social welfare in the Peruvian mining industry.